Improved Indonesian Language Learning Outcomes using Problem Based Learning Methods for Class III SD Students - Bangkit Subarkah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in Indonesian muples by using the problem based learning method. This research is a Classroom Action Research (PTK) using two cycles. Each cycle consists of planning, implementing, observing and reflecting. In this study using post tests. In the first cycle, 81% students completed while in the second cycle it was 100%. These results indicate that the Problem Based Learning method can improve the learning outcomes of Indonesian students in grade III SD Negeri Surorejo.